Household Behavior and Response to the Participative Institutional Model for the Program of Handling Drainage of Productive Cows - Ardi Novra; Bagus Pramusintho (Buletin Peternakan, 2019)
The research survey aimed to observe the households behavior and response to the participatory institution model of the preventing of the productive cows exploitation. The sample technique to select of the domestic cattle farmer (DCF) as the unit of analysis using the multiple stages cluster sampling and then sample allocation was equal for three districts. Structural equation model consisted of 5 behavior equations drawn up from the 5 endogenous and 13 exogenous variables. The research results showed that the rate of release of productive cows about 19.23 percent. The institutional model to handling of the drain at least productive cows have four major components, were members (DCFs), the management, micro-finance institutions (MFIs) and buffer-stock. The household motivation to develop the business scale and maintain the productive heifer shaped by land ownership and livestock scale expected factors. Then both types of motivation were not significantly associated with DCF's motivation to engage in institutional, as the more dominant individual as shaped by the farmer age. The other hand, the confidence level of participatory institutional effectiveness significantly shaped by the perception of institutional and potential release of productive heifer compared the potential release of motivation factors and correlated positively with the economic conditions.